The Impact of R&D on Sustainable Development: a Literature Review - U. B. Yussupov; M. K. Aliyev; A. A. Kazhmukhametova; L. Z. Aitkhozhina; B. A. Zhumatayeva (Экономика: стратегия и практика, 2023)
R&D is seen as crucial to achieving sustainable development, as it promotes innovation and drives economic growth. The aim of this work is to identify primary indicators of research and development and conduct an analysis of the research and development situation in Kazakhstan. The methodology consists of a systematic literature review (13 articles) and statistical analysis of research and innovation development in Kazakhstan for the period between 2014 and 2020 and included indicators of R&D development in Kazakhstan: R&D Costs Total/ Internal/ External and Sources of funding. Results show that research and development investments have a positive impact on productivity, innovation, and economic growth. The results showed that the highest level of internal costs for innovative research and development is formed in the cities of Almaty and Astana and in the Mangystau region. However, the level of internal research costs in Almaty c. decreased by 22% in 2018. Positive dynamics were in Astana, East Kazakhstan, Atyrau, Mangystau, Pavlodar and Zhambyl regions. There was also observed a clear upward trend in the own funds of enterprises allocated to finance these costs. The findings suggest that policymakers should prioritize supporting research and development and innovation investments in both the public and private sectors. Analysis of research and development expenses shows that internal costs are the most crucial, as they reflect the innovation demand and potential of enterprises. Further analysis is necessary to examine the distribution of internal costs based on the types of activities carried out by companies.